2019
DOI: 10.1609/aaai.v33i01.33017809
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Optimal Approximation of Discrete Random Variables for Estimation of Probabilities of Missing Deadlines

Abstract: We present an efficient algorithm that, given a discrete random variable X and a number m, computes a random variable whose support is of size at most m and whose Kolmogorov distance from X is minimal. We present some variants of the algorithm, analyse their correctness and computational complexity, and present a detailed empirical evaluation that shows how they performs in practice. The main application that we examine, which is our motivation for this work, is estimation of the probability of missing deadlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…It is interesting to look for optimal approximations. In [25], we showed that an optimal approximation of a single random variable can be obtained in polynomial time. Specifically, we showed that given a random variable X and a target support size m, we can find the minimal ε * and a variable X such that X has support of size m and X ≺ ε * X .…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to look for optimal approximations. In [25], we showed that an optimal approximation of a single random variable can be obtained in polynomial time. Specifically, we showed that given a random variable X and a target support size m, we can find the minimal ε * and a variable X such that X has support of size m and X ≺ ε * X .…”
Section: Discussionmentioning
confidence: 99%
“…al. [4,5]. These papers study approximations of random variables in the context of estimating deadlines.…”
Section: Related Workmentioning
confidence: 99%
“…al. in [4,5] handle this reduction using weaker or sub-optimal notion of approximation than ours, as discussed in Section 2.…”
Section: Experimental Evaluationmentioning
confidence: 99%
See 2 more Smart Citations